I'm having a little difficulty understanding how to find the strong form of a PDE given the weak form. For example, I have the weak form as:

$\displaystyle\int_\Omega [a(x)\nabla u\cdot\nabla v+b(x)uv] \space dx=-\int_\Omega fv\space dx$

where we have $u,v\in H^1_0(\Omega)$.

I know I am supposed to somehow get the $\nabla$ off of the $v$ in the first integral so that I can, effectively, write

$\int_\Omega F[u]v\space dx=-\int_\Omega fv\space dx$

for some function(al?) on $u$ from which I can extract my strong form PDE, but I'm not sure if (1) I'm thinking about this the correct way and if I am (2) how to go about doing this.

Any help/hints/tricks/suggestions are highly appreciated. Thanks in advance!


Let $A(x)$ be the $n\times n$ matrix of coefficients $$ A_{ij}(x)= \delta_{ij}a(x), $$ where $\delta_{ij}$ is the Kronecker delta; that is, $A(x)$ is a diagonal matrix with diagonal entries all equal to $a(x)$. (I think I'm interpreting the notation in the problem correctly, but the exposition that follows can be modified appropriately if I'm not.) Write $$ a(x)\nabla u\cdot\nabla v = \sum_i A_{ij}(x)u_{x_i}v_{x_i}, $$ Let $L$ be the differential operator so that the given weak form of the PDE is the weak formulation of $$ Lu = f. $$ Write $L = G + H$, where $G$ is the second-order differential term and $H$ is the zero-th order term. Then $G$ is the second-order operator $$ Gu = -\sum_{i=1}^n \left(A_{ii}(x)u_{x_i}\right)_{x_i}. $$ This is because if we formally integrate by parts in the weak formulation, we obtain $$ \int \sum_{i=1}^nA_{ii}u_{x_i}v_{x_i} = -\int \sum_{i=1}^n\left(A_{ii}u_{x_i}\right)_{x_i} v. $$ And in fact, for a strong solution this is exactly what we would expect for all test functions $v$. The advantage to using $\nabla u\cdot\nabla v$ is that we can put weaker regularity assumptions on the $u$ and $v$ used in the weak formulation (which is exactly the point of a weak formulation).

So to wrap up the story, $L$ is given by $$ Lu = -\sum_{i=1}^n \left(A_{ii}(x)u_{x_i}\right)_{x_i} - b(x)u. $$ Recalling that $A_ii(x) = a(x)$, we can express this as $$ Lu = -\sum_{i=1}^n a(x)u_{x_ix_i} - \sum_{i=1}^n a_{x_i}(x)u_{x_i} - b(x)u. $$ So the strong formulation of the PDE is $$ -\sum_{i=1}^n a(x)u_{x_ix_i} - \sum_{i=1}^n a_{x_i}(x)u_{x_i} - b(x)u = f. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.